The Influence of Integrity, Work Motivation and Work Discipline on Employee Performance at Bank Jambi Branch Sungai Penuh City - Meri Andayani; Dasman Lanin (Jurnal Ad'ministrare, 2022)
This study aims to provide evidence that: 1) To analyze the effect of integrity on employee performance at Bank Jambi Branch Kota Sungai Penuh; 2) To analyze the effect of work motivation on employee performance at Bank Jambi City Sungai Penuh Branch; 3) To analyze the effect of work discipline on employee performance at Bank 9 Jambi, Sungai Penuh Branch; 4) To analyze how much influence integrity, work motivation and work discipline have on the performance of employees at Bank 9 Jambi, Sungai Penuh Branch. By using the Slovin formula, the sample size can be measured, namely the number of employees who are sampled, with a total of 34 employees at Bank 9 Jambi City Sungai Penuh Branch. Data collection was carried out using a survey method with a questionnaire. The data analysis technique used in this research is descriptive and quantitative analysis. The data collected are primary and secondary data which can be classified as independent variables and dependent variables. Hypothesis testing in this study using multiple linear regression test. Based on the results of the study, it is known that: 1) Integrity has a positive and significant effect on partially employee performance at Bank 9 Jambi Branch Kota Sungai Penuh where Tcount is greater than Ttable where 5.891>2.032 with a significance of 0.000<0.05. 2) Work motivation has a positive and partially significant effect on employee performance at Bank 9 Jambi City Sungai Penuh Branch where Tcount is greater than Ttable where 6.753>2.032 with a significance of 0.000<0.05. 3) Work discipline has a positive and significant effect on partially employee performance at Bank 9 Jambi City Sungai Penuh Branch where Tcount is greater than Ttable where 5,911>2,032 with a significance of 0.000<0.05. 4) Simultaneously, integrity, work motivation and work discipline have a positive and significant effect on employee performance at Bank 9 Jambi, Sungai Penuh Branch.